The relation of the linguistic sign with the mind and cognitive processes: A conceptualization essay from a historical and cultural perspective - Gómez J., Luis Fernando (Rastros Rostros, 2012)
This paper is an essay on two fundamental principles (iconicity and motivation), that are fundamental in academic discussion on modern linguistics. The author claims that the distance between linguistic expressions may constitute an iconic index of the conceptual and psychological distance between the terms or events that said expressions denote. On the other hand, the length of an expression may also have a relationship with the degree in which the expression presents new or unknown information, and thus a reduced form may constitute an economically motivated index of familiarity.
Keywords: Economy; Icon; Motivation; Cognitive process; Linguistic sign